Mendiola massacre [videorecording] - Regalado, Nonoy ([Quezon City] Asia Visions, 1988)
A short documentary on the 22nd of January 1987 massacre of farmers at Mendiola bridge.
Kamera, Nonoy Regalado; tunog, Gil Magalong; musika, Buklod
Keywords: Massacres -- Philippines; Land reform -- Philippines